Legal options for notaries/ppat for forged letters in the land mafia case (nirina zubir case study) - Bahira Nur Salma; Aju Putriyanti (Trigin Publisher, 2023)
The current analysis focuses on the consequences of the law with regard to the notary's performance of an authentic act. An authentic deed is a very important piece of evidence in the context of civil law, but if a notary is unable to execute an act of oath, then administrative, criminal and civil sanctions may result. The Sanctions in question is governed by the Notary Office Regulations, the Civil Code, and other Statutory Regulations. The current study employs the normative method of legal analysis by conducting an analysis of each rule of procedure that has an impact on the legal consequences of the notary's possible falsification of the act. According to the study's findings, if a notary fails to complete an act of oath, they may be required to submit administrative sanctions such as a certificate of notarial competence, procedural sanctions such as a prison sentence or fines, and substantive sanctions such as a lawsuit cancellation of the civil act. In this essay, it is also discussed how to apply the law in the event of an opportunistic forgery act in a mafia-related case. Affected parties can request a lawsuit for canceling a civil deed to the court if an authentic counterfeiting act occurs in a land mafia case. However, if the notary is in trouble with the ostensible act in question, he or she may be recognized as an administrative sanction, a criminal, and a civil in accordance with the applicable statutory rules.